Risk of intraoperative floppy iris syndrome among selective alpha-1 blockers—A consistency model of 6,488 cases - Wang, Ya-Hui; Huang, Liang-Chen; Tsai, Sung Huang Laurent; Chen, Ying-Jen; Wu, Chien-Liang; Kang, Yi-No (Frontiers in Medicine, 2022)
Selective α1-blockers are commonly administered to patients with lower urinary tract syndrome and benign prostatic hyperplasia, but may increase the risk of intraoperative floppy iris syndrome (IFIS). The purpose of this study aimed to clarify the risk of IFIS among various selective α1-blockers. Four databases were searched for prospective studies comparing alpha-1-antagonists. Data were pooled using the consistency model, and used risk ratio (RR) and mean difference (MD) for IFIS and pupil diameter, respectively. This study finally included 25 prospective comparative studies. Based on 51 direct comparisons with 6488 cases, risks of IFIS in patients who received tamsulosin [RR, 13.85; 95% confidence interval (CI): 7.34 to 26.11], terazosin (RR, 8.94; 95% CI 2.88 to 27.74), alfuzosin (RR, 7.73; 95% CI: 3.05 to 19.62), and doxazosin (RR, 3.88; 95% CI: 1.13 to 13.28) were significantly higher than those did not receive α1-antagonists. Based on 11 direct comparisons with 564 cases, as compared to no α1-antagonists, patients who received tamsulosin (MD, −0.36; 95% CI: −0.71 to −0.01) and alfuzosin (MD, −0.34; 95% CI: −0.62 to −0.07) showed smaller pupil diameter under mesopic light levels, while those received silodosin did not show significantly smaller mesopic pupil diameter than people without α1-antagonists. IFIS seems to be inevitable with the usage of α1-antagonists, and tamsulosin needs to be cautious due to the significantly higher risk of severe IFIS. With regard to silodosin, there is no strong evidence to support the uses of italthough it does not significantly decrease mesopic pupil diameter.